IMPLEMENTASI TATA KELOLA PERUSAHAAN MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILITY PADA BANK BTN CABANG AMBON - BARUS UMARELLA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this study is to find out how the implementation of good corporate governance through the implementation of corporate social responsibility (CSR) in an effort to improve the performance and reputation of the company. The analysis technique used is qualitative descriptive analysis with data collection methods of observation, interviews and evaluation of documents related to research. The results of the study showed that good corporate governance (GCG) carried out through the CSR activities of the Ambon branch of BTN bank went well and had a good impact as well on society and company performance. Good governance will greatly affect the implementation of CSR and directly on the reputation of the company so it is highly recommended for each company to implement and implement a governance system that can make a positive contribution both internal and external.